Prevailing breast feeding practices of infants attending paediatric out-patient department - R, Manjunatha Swamy; Patil, Ravindra B.; ., Venugopal (International Journal of Research in Medical Sciences, 2017)
Background:Objectives of current study were to know the prevailing infant feeding practices in infants and to identify the problems affecting infant and young child feeding practices and to analyze the environmental factors influence the mothers, families and caregivers in infant feeding. Methods:The present study is a hospital based observation study. A total of 501 mothers and their infants attending new born paediatric OPD, immunization clinic of department of paediatrics for various reasons of health care were recruited for the study after their informed consent and institutional ethical clearance. Information about the first feed after birth, time of initiation of breastfeeding, duration of exclusive breast feeding, time of introduction of complementary feeding, knowledge of feeding skills, mother’s concept of adequacy of breast milk were collected in the structured, pre tested proforma by personal one to one interview with the mothers. All the mothers of infants from 0 to 1 year were included. Statistical analysis: The data obtained by the interview were analyzed with regarding to mothers education level, religion and other related parameters pertaining to feeding practices. Percentages of parameters were calculated and analyzed. Results:Majority of the mothers belong to the age group of 18 to 30 years (96.01%), prelacteal feeds were given by a good number of mothers (42.32%), 60.66% mothers were given the sugar water as the prelacteal feed and 71.56% mothers have used cup and spoon to give prelacteal feeds. 75.25% of the mothers have practiced giving colostrum, 72.26% of mothers were breastfeeding their baby for 5 to 10 minutes during each feed at an interval of 0.5 hours to 3.5 hours. Majority of mothers (34.73%) had the knowledge of starting of weaning at six months and 46.88% of mothers were giving weaning food twice daily. Conclusion:Significant number of mothers had discarded colostrum and most of the mothers intended to give only breast milk upto four months and they did not have correct knowledge regarding exclusive breastfeeding upto six months.